Advances in Nanotheranostics II Cancer Theranostic Nanomedicine - Dai, Zhifei (Springer Series in Biomaterials Science and Engineering, 2016)
This book surveys recent advances in theranostics based on magnetic nanoparticles, ultrasound contrast agents, silica nanoparticles and polymeric micelles. It presents magnetic nanoparticles, which offer a robust tool for contrast enhanced MRI imaging, magnetic targeting, controlled drug delivery, molecular imaging guided gene therapy, magnetic hyperthermia, and controlling cell fate. Multifunctional ultrasound contrast agents have great potential in ultrasound molecular imaging, multimodal imaging, drug/gene delivery, and integrated diagnostics and therapeutics. Due to their diversity and multifunctionality, polymeric micelles and silica-based nanocomposites are highly capable of enhancing the efficacy of multimodal imaging and synergistic cancer therapy. This comprehensive book summarizes the main advances in multifunctional nanoprobes for targeted imaging and therapy of gastric cancer, and explores the clinical translational prospects and challenges. Although more researchis needed to overcome the substantial obstacles that impede the development and availability of nanotheranostic products, such nontrivial nanoagents are expected to revolutionize medical treatments and help to realize the potential of personalized medicine to diagnose, treat, and follow-up patients with cancer. Zhifei Dai is a Professor at the Department of Biomedical Engineering, College of Engineering, Peking University, China.